Reduced Gravity and Magnetohydrodynamic Effects on Transient Mixed Convection Flow Past a Magnetized Heated Cone Embedded in Porous Medium - Hossam A. Nabwey; Zia Ullah; Asifa Ilyas; Muhammad Ashraf; Ahmed M. Rashad; Sumayyah I. Alshber; Miad Abu Hawsah (Journal of Mathematics)
The effects of reduced gravity on the periodic behavior of convective heat transfer characteristics of fluid flow along the magnetized heated cone embedded in porous medium is studied in the current contribution. The mathematical form of the nonlinear partial differential equations subject to the boundary conditions for the proposed unsteady model is presented. By employing appropriate dimensionless quantities, the mathematical equations are transformed into dimensionless form to get the numerical solutions of the proposed model. The dimensionless form is further condensed to a form that is more straightforward for smooth numerical computations. Later, large simulations are run using the implicit finite difference method for appropriate range of parameters values included in the flow model. The effect of reduced gravity parameter Rg, the Richardson parameter or mixed convection parameter λ, the Prandtl number Pr, and the porosity parameter Ω, on chief physical quantities, that is, velocity profile, temperature distribution, magnetic intensity, transient skin friction, transient rate of heat transfer, and transient current density are simulated and highlighted graphically. Additionally, via careful examination and intentional discussion of physical reasoning, the physical impacts of various factors on the material qualities are examined. Applications that motivate the present work is the reduced gravity effects due to which the other nongravity forces such as thermal volume expansion, density difference, and magnetic field can induce the fluid motion.